Sostenibilidad del volumen de cosecha calculado con el Método Mexicano de Ordenación de Montes - Torres Rojo, Juan Manuel (Instituto de Ecología, A.C., 2016)
An analysis considering the effect of harvest volume estimated through the Mexican Method of Forest Regulation (MMFR) on the sustainability of forest is presented. The analysis postulates that growth projection of a forest population must follow a logistic behavior, instead of an exponential behavior as assumed by the MMFR. When growth projection follows a logistic behavior, then harvest regulation is possible in the long run and it is easy to identify criteria to evaluate sustained yield and the sustainability of the residual forest in the short run. In addition, it is possible to identify economically optimal harvest volumes. On the other hand, the assumption of exponential growth does not allow neither harvest regulation nor sustainability criteria identification. In addition it is not possible to estimate an economically optimal harvest volume. Results show that the assumption of exponential growth from the MMFR must be modified and the management of residual forest structures must be emphasized in order to achieve sustainability on the Mexican forests managed under an irregular system.